Device representatives in hospitals: are commercial imperatives driving clinical decision-making?. Issue 9 (4th July 2018) - Grundy, Quinn; Hutchison, Katrina; Johnson, Jane; Blakely, Brette; Clay-Wlliams, Robyn; Richards, Bernadette; Rogers, Wendy A
Abstract : Despite concerns about the relationships between health professionals and the medical device industry, the issue has received relatively little attention. Prevalence data are lacking; however, qualitative and survey research suggest device industry representatives, who are commonly present in clinical settings, play a key role in these relationships. Representatives, who are technical product specialists and not necessarily medically trained, may attend surgeries on a daily basis and be available to health professionals 24 hours a day, 7 days a week, to provide advice. However, device representatives have a dual role: functioning as commissioned sales representatives at the same time as providing advice on approaches to treatment. This duality raises the concern that clinical decision-making may be unduly influenced by commercial imperatives. In this paper, we identify three key ethical concerns raised by the relationship between device representatives and health professionals: (1) impacts on healthcare costs, (2) the outsourcing of expertise and (3) issues of accountability and informed consent. These ethical concerns can be addressed in part through clarifying the boundary between the support and sales aspects of the roles of device representatives and developing clear guidelines for device representatives providing support in clinical spaces. We suggest several policy options including hospital provision of expert support, formalising clinician conduct to eschew receipt of meals and payments from industry and establishing device registries.